Immunosuppression associated with interleukin-1R-associated-kinase-M upregulation predicts mortality in Gram-negative sepsis (melioidosis). - Wiersinga, W; van't Veer, C; van den Pangaart, P; Dondorp, A; Day, N; Peacock, S; van der Poll, T (2009)
OBJECTIVES: Sepsis is associated with immunosuppression (characterized by a reduced capacity of circulating monocytes to release proinflammatory cytokines), which has been implicated in late mortality. Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, is an important cause of community-acquired sepsis in Southeast Asia with a mortality of up to 40%. Previous in vitro and murine studies have suggested a key role for the so-called negative regulators of the toll-like receptor (TLR) signaling pathway in immunosuppression. In this study, we investigated the expression of these negative TLR regulators in patients with septic melioidosis in association with the responsiveness of peripheral blood leukocytes of these patients to lipopolysaccharide and B. pseudomallei. DESIGN: Ex vivo study. SETTING: Academic research laboratory. PATIENTS: Thirty-two healthy controls and 34 patients with sepsis caused by B. pseudomallei. INTERVENTIONS: None. MEASUREMENTS: 1) Plasma cytokine levels; 2) ex vivo cytokine production capacity of whole blood; and 3) purified mononuclear cell-derived messenger RNA (mRNA) levels of key inhibitory molecules of the TLR-signaling cascade were investigated. MAIN RESULTS: In accordance with an immunosuppressed state, whole blood of patients demonstrated a strongly decreased capacity to release the proinflammatory cytokines tumor necrosis factor-[alpha], interleukin-1[beta], and the chemokine interleukin-8 after ex vivo stimulation with lipopolysaccharide or B. pseudomallei. Analysis of myeloid-differentiation-88-short, interleukin-1R-associated-kinase (IRAK)-M, IRAK-1, suppressor-of-cytokine signaling-3, Src-homology-2-domain-containing inositol-5-phosphatase-1, single-immunoglobulin-interleukin-1R-related-molecule, and A20 mRNA expression in purified mononuclear cells showed decreased IRAK-1 and elevated IRAK-M expression in patients with septic melioidosis. Immunosuppression was correlated with mortality; furthermore, patients who eventually died had higher IRAK-M mRNA levels on admission than the patients who survived. CONCLUSIONS: Immunosuppression in sepsis caused by B. pseudomallei is associated with an upregulation of IRAK-M and an indicator of poor outcome.